2009
DOI: 10.1007/s12288-009-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Red cell alloimmunization in multitransfused patients and multiparous women

Abstract: Purpose To determine the incidence of alloimmunization against red cell antigens and the thermal amplitude and specifi city of antibodies in multitransfused patients and multiparous women.Methods Antibody screening was performed in 30 nontransfused orthopedic surgery cases (control), 504 multitransfused patients and 325 multiparous women. Antibody screening at 4°C, 22°C and 37°C was carried out in a saline phase, by indirect antiglobulin technique (IAT), using papain cystein, low ionic strength solution (LISS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
(11 reference statements)
2
14
1
Order By: Relevance
“…Thereby, antibodies arise in the chronic renal failure patients after exposure to multiple of red blood cell transfusions. 4 We observed of alloimmunization prevalence was 18 % detected in 7 out of 39 CRF patients, this finding is higher than the frequency of previous studies have done in Sudan country that they reported of prevalence 13.1 % 4 , Similarly study by Domen and Ramirez showed the rate 6.1 % 10 and frequency of 9.9 % reported by Shukla 2 in CRF patients undergoing dialysis while study by Patel et al 11 had been shown that the alloimmunization rate 8.2 % in CRF patients.…”
Section: Discussion:-contrasting
confidence: 50%
“…Thereby, antibodies arise in the chronic renal failure patients after exposure to multiple of red blood cell transfusions. 4 We observed of alloimmunization prevalence was 18 % detected in 7 out of 39 CRF patients, this finding is higher than the frequency of previous studies have done in Sudan country that they reported of prevalence 13.1 % 4 , Similarly study by Domen and Ramirez showed the rate 6.1 % 10 and frequency of 9.9 % reported by Shukla 2 in CRF patients undergoing dialysis while study by Patel et al 11 had been shown that the alloimmunization rate 8.2 % in CRF patients.…”
Section: Discussion:-contrasting
confidence: 50%
“…Other study from Sharkia reported alloimmunization rate of 9.5 % in multiple transfused patients [14] while study by Patel et al [15] had been shown that the alloimmunization rate 8.2 % in CRF patients. The differences in the alloinummization rate were attributed to: Heterogeneity among the population, in pre-transfusion test blood were matched only for ABO and Rh(D)antigens, sample size of study population and sensitivity of the test method .…”
Section: Discussionmentioning
confidence: 99%
“…10 There have been a few studies from different parts of world that have demonstrated the presence of alloantibodies in thalassemia patients, Sickle cell disease patients, and also chronic renal disease patients. 7,8,14 This study was undertaken to determine the frequency and specificity of RBC alloantibodies among the chronic renal failure patients of Jammu region which have not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell alloantibodies can develop in approximately 6-36% of patients who receive repeated transfusion. 7,8 Various factors influence alloantibody formation in our body including the number and frequency of the transfusions as well as the recipient's sex, age, immune status and underlying disease. [9][10][11] The antibodies thus formed result in difficulty in cross matching, various types of transfusion reactions, haemolysis and other potentially life-threatening events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation